Quality of Irrigation Waters of Kanjhwala and Alipur Blocks of Delhi in Relaton to Soil Properties and Growth of Wheat - Paliwal, K V; Dinesh, Raghubir Singh (Annals of Arid Zone, 2016)
Thirty representative irrigation waters were collected from the wells of Kanjhwala and Alipur blocks of Delhi to examine their quality according to various classifications and their effect on soil properties. Observations on the growth of wheat revealed that none of the classifications is fully applicable for judging the suitability of these waters for wheat. Growth was very poor at an electrical conductivity of 17.6m mhos/cm and SAR of 38.5 of the saturation extract and sodium saturation of 22.1 per cent. Inspite of using highly saline irrigation waters, these soils are not much salinized or sodiumised due to flooding conditions. While judgina the suitability of irrigation waters due consideration should be given to topography, drainage characteristics and moisture relationships. There was no equilibrium between irrigation water and soil solution and indices. based 00 saturation extract could predict better than quality of irrigation waters. Both soluble sodium percentage and SAR of the saturation extract correlated significantly with the ESP of soils. A better correlation was observed between SAR of the saturation extract and exchangeable sodium ratio.